Making a Difference Progressive Values in Public Administration - Richard C. Box (M.E.Sharpe, 2008)
Public administration is an applied professional fi eld of study and practice; hence, much of the content of academic coursework in the fi eld is about technical matters. Even so, it is a common experience for those who teach public administration to encounter studentsâ€”both experienced professionals and people yet to begin their careersâ€”who care deeply about the people and places they serve and have a broad sense of public service in society. These are people who want to â€œmake a difference,â€ and they may be aware of tension between their desire for constructive change and political and economic conditions that make change diffi cult.